Serum Paraoxonase Activity In "Post-Menopausal" Women - SUMAN UMESHCHANDRA,; UMESHCHANDRA D.G,; S.M AWANTI, (International Journal of Pharma and Bio Sciences, 2012)
Coronary artery disease (CAD) is the most important cause of death and disability among older women; by the year 2015 cardiovascular mortality is likely to rise to 90% in females in India. High circulating serum total cholesterol (TC), low density lipoproteins (LDL) and triglyceride (TG) are major risk factors of this disease. Paraoxonase is an serum esterase associated with high density lipoprotein (HDL) and contributes to protect against low density lipoprotein oxidation [1]. “Post-menopausal” women are known to have altered lipid profile; hence present study is designed to estimate serum paraoxonase activity and correlate with lipid profile in “post-menopausal” women. The study was conducted on 55 post menopausal women with no history of hypertension and diabetes and 57 healthy controls. Serum paraoxonase activity was estimated by spectrophotometric method and lipid profile by enzymatic assay methodSerum paraoxonase activity and HDL-C levels were low and total cholesterol, triglycerides and low density lipoproteins levels were high in post menopausal women compared to healthy controls (p<0.01). Serum paraoxonase activity correlated positively with HDL-C (p<0.01). This may indicate the susceptibility of post menopausal women to accelerated atherogenesis leading to coronary artery disease.